Pengembangan modul pesawat sederhana berbasis problem based learning untuk meningkatkan pemahaman peserta didik - Ntelok, Zephisius Rudiyanto Eso; Jamun, Yohannes Marryono; Hasni, Maria (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research at SDK Santa Agnes Ruteng IV. This study was intended to develop teaching materials for science subjects on the topic of Simple Machines to Enhance the Understanding of Grade IV Students. The method applied in this research was Research and Development (R & D) utilizing the ADDIE framework. ADDIE stands to Analyse, Design, Development, Implementation, Evaluation, which are stages in the research process. However, due to the time constraints and limitations in the researcher's abilities, the development model in this study was limited to four stages: analysing, design, development, and implementation. The module was developed and structured through a validation process by experts in the fields of content, media, and language. The average validation scores obtained from content experts were 3.46, categorized as valid; media experts scored 3.83, also categorized as valid; and language experts scored 3.50, categorized as valid. Thus, the overall average validation score from the three expert assessments was 3.59, and based on the validity categorization criteria, the teaching module fell into the